Effects of servant leadership on gratitude, empowerment, innovativeness and performance: Turkey example - Baykal, Elif; Zehir, Cemal; Köle, Mahmut (Istanbul Univ, 2018)
Inspired by positive organizational scholarship, this study focuses on two important concepts of positive organizational behavior: empowerment and gratitude. The effects of servant leadership style-with its ever-increasing popularity-were investigated based on these two concepts, under the assumption that having been affected by servant leadership, gratitude and empowerment will enhance the innovative capacity of the individuals on whom it is tested. The assumption is that this change, in turn, will have a positive effect on the overall performance of the organization. During our field survey, 527 white-collar workers from Turkey's Marmara region contributed to the study. Our results suggest that servant leadership has a positive effect on the perceptions of empowerment and gratitude felt by followers, and that these feelings in turn affect innovativeness and organizational performance. We thus contribute to the related literature by displaying the positive effects of innovativeness on organizational performance by supporting the view that when firms are more innovative they tend to perform better.

Bu çalışmada, pozitif örgüt okulundan esinlenilerek, iki önemli pozitif örgütsel davranış kavramı olan, güçlendirme ve şükran duyguları üzerine odaklandık. Bu araştırmada, popülerliği her geçen gün artan hizmetkar liderlik tarzının, yukarıda bahsi geçen iki kavram üzerindeki etkisi araştırılmış ve hizmetkar liderlik tarzından etkilenerek, şükran duygusu ve güçlendirmenin bireylerin yaratıcılık kapasitelerini arttıracağı öngörüsü test edilmiştir. Ve bu durumun da örgütün genel performansını pozitif yönde etkileyeceği öngörülmüştür. Saha araştırmamızda, Türkiye'de, Marmara Bölgesinde çalışan 527 beyaz yakalı çalışan araştırmaya katkıda bulunmuştur. Çalışmanın sonucunda, hizmetkâr liderliğin, takipçilerin hissettiği güçlendirme ve şükran duyguları üzerinde olumlu etkileri olduğu ve bu duyguların yenilikçiliği ve örgütsel performansı etkilediği kanıtlanmıştır. Sonuçlar, yenilikçiliğin örgütsel performans üzerindeki olumlu etkilerini göstererek ilgili literatüre katkıda bulunmuş ve firmaların daha yenilikçi olduklarında daha yüksek performans seviyeleri gösterme eğilimininde olduklarını desteklemiştir.
Hizmetkar liderliğin şükran duygusu, güçlendirme, yenilikçilik ve performans üzerine etkisi: Türkiye örneği
WOS: 000437199300002
Keywords: Servant Leadership; Gratitude; Innovativeness; Hizmetkar Liderlik; Şükran; Yenilikçilik